2003
DOI: 10.1080/10473289.2003.10466301
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption Characteristics of Semiconductor Volatile Organic Compounds on the Thermal Swing Honeycomb Zeolite Concentrator

Abstract: The use of a honeycomb zeolite concentrator and an oxidation process is one of the most popular methods demonstrated to control volatile organic compound (VOCs) emissions from waste gases in semiconductor manufacturing plants. This study attempts to characterize the performance of a concentrator in terms of the removal efficiencies of semiconductor VOCs (isopropyl alcohol [IPA], acetone, propylene glycol methyl ether [PGME], and propylene glycol monomethyl ether acetate [PGMEA]) under several parameters that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…But when high boiling-point VOCs are treated during desorption process, they tend to gradually occupy the adsorption sites and deteriorate the performance of an adsorber [4]. The installation of condensers before a VOCs adsorber to condense the high boiling-point VOCs may be an effective method to prevent the decreasing of VOCs removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But when high boiling-point VOCs are treated during desorption process, they tend to gradually occupy the adsorption sites and deteriorate the performance of an adsorber [4]. The installation of condensers before a VOCs adsorber to condense the high boiling-point VOCs may be an effective method to prevent the decreasing of VOCs removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the concentrated VOCs are further treated by incineration devices. The initial operation efficiencies of zeolite concentrators in terms of total hydrocarbon (THC) emitted from semiconductor fab are well above 90% in laboratory tests [2][3][4][5][6] and field operations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The central abatement systems in each fab model include a central acid scrubber, an ammonia scrubber, a volatile organic compound (VOC) oxidizer and an acid waste neutralization unit as well as copper CMP and fluoride wastewater treatment systems. The abatement efficiencies of these central systems for gaseous acids, ammonia and VOCs and are based on measurements published by semiconductor industry members [91,60,16,17,97,90]. Conversion of liquid waste is calculated based on expected reactions and the pH requirements of effluents to the public water treatment system.…”
Section: Abatementmentioning
confidence: 99%
“…Molecular sieve [15,16] has been studied for the removal of volatile organic compounds (VOCs), and it gradually substitutes for activated carbon in reducing VOC emissions from the semiconductor and optoelectronic industries. [17] However, only a few researches [18] on removing PH 3 by molecular sieve dry adsorption have been studied. In this study, Li Wen-Chih reported the maximum adsorption capacity was 31 mg of PH 3 /g of adsorbents for both Cu/ZSM-5 and Cu/Y zeolites.…”
Section: Introductionmentioning
confidence: 99%